Maternal Work and Spontaneous Preterm Birth: A Multicenter Observational Study in Brazil - Buen, Mariana; Amaral, Eliana; Souza, Renato T.; Passini, Renato; Lajos, Giuliane J.; Tedesco, Ricardo P.; Nomura, Marcelo L.; Dias, Tábata Z.; Rehder, Patrícia M.; Sousa, Maria Helena; Cecatti, José Guilherme; Marba, Sérgio T.; et al. (Springer Nature, 2020)
Spontaneous preterm birth (sPTB) is a major pregnancy complication involving biological, social, behavioural and environmental mechanisms. Workload, shift and intensity may play a role in the occurrence of sPTB. This analysis is aimed addressing the effect of occupational activities on the risk for sPTB and the related outcomes. We conducted a secondary analysis of the EMIP study, a Brazilian multicentre cross-sectional study. For this analysis, we included 1,280 singleton sPTB and 1,136 singleton term birth cases. Independent variables included sociodemographic characteristics, clinical complications, work characteristics, and physical effort devoted to household chores. A backward multiple logistic regression analysis was applied for a model using work characteristics, controlled by cluster sampling design. On bivariate analysis, discontinuing work during pregnancy and working until the 7th month of pregnancy were risks for premature birth while working during the 8th - 9th month of pregnancy, prolonged standing during work and doing household chores appeared to be protective against sPTB during pregnancy. Previous preterm birth, polyhydramnios, vaginal bleeding, stopping work during pregnancy, or working until the 7th month of pregnancy were risk factors in the multivariate analysis. The protective effect of variables compatible with exertion during paid work may represent a reverse causality. Nevertheless, a reduced risk associated with household duties, and working until the 8th-9th month of pregnancy support the hypothesis that some sort of physical exertion may provide actual protection against sPTB.